3D nanoporous Fe, N-doped carbon architecture derived from polymerized hemoglobin for highly efficient oxygen reduction reaction. Issue 11 (2nd November 2021) - Yang, Yu Jun; Li, Weikun
Abstract: A 3D nanoporous Fe, N-doped carbon architecture (CHbG) was prepared by simply carbonizing the hemoglobin glutamer (HbG), the polymerized hemoglobin (Hb) with glutaraldehyde as the cross-linking agent. As cathodic catalyst for oxygen reduction reaction (ORR), CHbG shows onset potentials of 0.87 V vs. reversible hydrogen electrode (RHE) in 0.1 M KOH which is as good as commercial Pt/C catalyst. The ORR catalyzed by CHbG follows 4-electron mechanism and shows good catalytic stability and high methanol tolerance in basic media.